The reality of the dimension of participation in decision-making in quality of work from the viewpoint of female faculty members in the College of Education at the University of Jeddah - Abuhussein, Ghada Ali; Salamah, Ebtisam Khalid Yahya (Journal of Educational and Psychological Sciences, 2021)
The study aimed to find out the degree of participation in decision-making related to the quality of work life of female faculty members at the College of Education, University of Jeddah. Where the descriptive survey approach was used in a comprehensive inventory method for the entire research community to collect data from the study population through a questionnaire that was prepared by the researcher for this purpose. The study population consisted of all the female members of the faculty of the College of Education at the University of Jeddah (Professor, Associate Professor, Assistant Professor, Lecturer, Instructor) and the numbers of (92) members for the academic year 1441-1442 AH, and receive (79) member respond, or 86% responded. The results found that the responses of faculty members were neutral regarding the availability of participation in decision-making. This result indicates that participation in decision-making is available to a moderate degree from their point of view. Among the most important recommendations of the researcher were the following:- Ensuring the participation of faculty members in management, making and making decisions that affect their work, and encouraging them to do so to ensure their implementation and take the responsibility towards of these decisions.- Opening the door for participation by faculty members to assist the college administration in contributing to solving problems of its departments.- Providing faculty members with the opportunity to choose the courses they want to teach.
Keywords: Quality; QWL; Decision-Making; Faculty of Education; University of Jeddah